2005
DOI: 10.1016/j.jacc.2005.06.068
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Coronary Artery Atherosclerosis in Patients With Erectile Dysfunction

Abstract: Coronary atherosclerosis is more severe in patients with vascular ED; ED predicts the presence and extent of subclinical atherosclerosis independent of traditional risk factors for cardiovascular disease. Thus, ED may be considered an additional, early warning sign of coronary atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
146
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(154 citation statements)
references
References 18 publications
4
146
0
4
Order By: Relevance
“…8 Men with ED with and without obesity have higher levels of C-reactive protein compared to men with normal erectile function. 6,7,9 Tumor necrosis factor-a, interleukin-6, C-reactive protein and reactive oxygen species all cause insulin resistance. Insulin is an integral stimulator of vascular NO and thereby increased skeletal muscle glucose disposal.…”
Section: Weight Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Men with ED with and without obesity have higher levels of C-reactive protein compared to men with normal erectile function. 6,7,9 Tumor necrosis factor-a, interleukin-6, C-reactive protein and reactive oxygen species all cause insulin resistance. Insulin is an integral stimulator of vascular NO and thereby increased skeletal muscle glucose disposal.…”
Section: Weight Lossmentioning
confidence: 99%
“…flow-mediated dilation (FMD) was 2.4±0.21% in the men with ED compared with 3.9 ± 0.26% in the men without ED (Po0.001). 7 This review will discuss various lifestyle and metabolic factors influencing vascular NO and erectile function, with an emphasis on the role of oxidative stress and inflammation, and specific interventions available to maximize erectile and vascular health.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 ED can be an early marker for atherosclerosis, cardiovascular risk and subclinical vascular pathology. 17,19,20,23 It can also be predictive of the presence and extent of subclinical atherosclerosis, independent of traditional risk factors. 21 The overall ED prevalence in men with coronary artery disease seems to be high.…”
Section: Introductionmentioning
confidence: 99%
“…Kaiser et al 29 were able to demonstrate worsened FMD in 30 men with ED without manifest CAD. Chiurla et al 80 had similar findings in 70 men with ED, as opposed to better endothelial function in 73 men without ED, again in patients without manifest CAD (although results also correlated with higher calcium scores). In addition, Yavuzgil et al 81 found vasculogenic ED to be associated with impaired FMD.…”
Section: Physiological Measurementsmentioning
confidence: 76%